Effects of temperature, relative humidity, and protective netting on Tyrophagus putrescentiae (Schrank) (Sarcoptiformes: Acaridae) infestation, fungal growth, and product quality of dry cured hams. (June 2018) - Hendrix, Jasmine D.; Zhang, Xue; Campbell, Yan L.; Zhang, Li; Siberio, Lurdes; Cord, Christine Leick; Silva, Juan L.; Goddard, Jerome; Kim, Taejo; Phillips, Thomas W.; Schilling, M. Wes.
Abstract: Since methyl bromide is an ozone depleting substance, there is a need to find effective alternative methods to control mite infestations on dry cured hams. Therefore, the objective of this study was to determine the most effective relative humidity and/or temperature combination to minimize mite reproduction and mold growth on dry cured hams in untreated and food-grade ingredient infused nets. Food grade coating formulations of 1) xanthan gum and propylene glycol, and 2) carrageenan, propylene glycol alginate, and propylene glycol nets were infused into nets. Dry cured ham cubes and slices were wrapped with untreated and treated nets, inoculated with 20 large mixed-sex mites per cube or 50 large mixed-sex mites per slice, and then stored for 14 d at each temperature (24, 28, and 32 °C) and RH (55, 65, 75, and 85%) combination in an environmental chamber. Tyrophagus putrescentiae on ham slices in untreated nets were reduced from the initial inoculum level of 50 mites per ham slice when exposed to 85% r.h. at 24, 28, and 32 °C. Nets infused with xanthan gum and propylene glycol or carrageenan, propylene glycol alginate, and propylene glycol, completely inhibited mite reproduction at 85% r.h. In addition, the nets infused with carrageenan, propylene glycol alginate, and propylene glycol, controlled mite reproduction below the initial inoculum level on ham cubes and ham slices at all temperatures and relative humidities that were evaluated. Six to eight trained panelists rated the amount of mold on the ham slice surfaces on a 0–100% scale and both treated nets evaluated were effective at preventing mold growth on the ham slices. Highlights: Treated nets maintained the mite count on ham cubes below the inoculum level. Minimum mite growth occurred on ham slices in untreated and treated nets at 85% RH. Treated nets were effective at controlling mite reproduction and mold growth.